Which factors are associated with the functional recovery in patients undergoing endoprosthetic knee reconstruction following bone tumour resection? – A observational study - Morri, Mattia (Arch Physiother, 2018)
BACKGROUND: The aim of the present study was to explore whether control of balance and other factors were associated with functional recovery and walking performance in the short term in a group of patients receiving modular knee endoprosthetic reconstruction following bone tumour resection in order to provide effective suggestions for a new rehabilitation protocol. METHODS: A cross-sectional study was carried out in the chemotherapy ward of an Italian hospital specialized in bone cancer. All patients consecutively treated using a modular knee endoprosthetic between January 2013 and February 2014 were included in the study. One year after surgery, various measuring instruments were used to assess the functional outcome achieved: Musculoskeletal Tumor Society rating scale, Toronto Extremity Salvage Score and specific motor tests of gait, such as gait speed and resistance. Data concerning the variables involved are as follows: bone resection, knee joint range of motion, quadriceps muscle strength and posture control. Statistical tests included correlation analysis (Pearson and Spearman correlation). RESULTS: Balance control was significantly correlated to all the gait tests performed. Age, duration of chemotherapy and strength of the knee extensor muscles also showed a correlation. Conversely, joint range of motion and resection percentage did not show a significant correlation. CONCLUSIONS: Rehabilitation in patients undergoing knee joint reconstruction due to cancer should include balance control exercises, which involve not only the treated limb but address the entire sensory and motor system. This extends beyond the concept of treatment aimed at improving individual functions such as joint range of motion and muscular strength.